Rising incidence of hip fractures in Sindhudurg west coast of Maharashtra, South India (2000 to 2011) - Kulkarni, Raghavendra S.; Kulkarni, Aditya P.; Kulkarni, Rachana A.; Kulkarni, Ranjani R.; Deshpande, R. S.; Kulkarni, Sriram R. (International Journal of Research in Orthopaedics, 2020)
Background: The incidence of hip fractures in Sindhudurg, west coast of Maharashtra has been reported in relation to age and gender. Methods: Using the medical records and X-ray registers from May 2000 to October 2011, all patients of proximal femoral fractures were recorded and included in this study. The data was cross checked doubly with details of indoor case papers against ward admission and operation theatre registers, were found to be congruent after verifying the names of patients. Results: The total male incidence was bimodal with moderate peaks at 31 to 50 years and very high at 51 to 70 years. The female incidence with peaks at 41 to 60 years with regular steady increase up to 80 years. Males of 31 to 70 years 2.5 times more likely to sustain a fracture (95% CI 2.3 to 2.8) than females. Females between 40 to 60 years 2.8 times more likely to sustain fracture than males (95% CI 2.5 to 3.0). The trend was stable from year to year. This high increase in hip fractures in men of 51 to 70 years incidence documented osteoporotic fractures in contrast with too much emphasis on the importance of menopause in hip fractures. Conclusions: Despite wide variations in age specific hip fracture rates over a decade, reasons for differences are not clear. From 2000 to 2011, the hip fractures in district hospital increased by a factor of 6.6%, 14.34% in both the genders above the age of 41 years in parallel with hospital admissions.